2014
DOI: 10.2535/ofaj.91.45
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Celiac and Superior Mesenteric Arteries in a Common Trunk - Description of a Rare Vessel Variation of the Celiacomesenteric Trunk with a Literature Review

Abstract: Summary: A variation artery was observed in a Japanese cadaver. The celiac and superior mesenteric arteries arose from a common trunk (also referred to as the celiacomesenteric trunk), but not from the abdominal aorta, respectively. From the common trunk, the common hepatic artery was distributed in the right part of the liver, and the left hepatic artery arose from the left gastric artery, which also arose from the common trunk. The left inferior phrenic artery arose from the common trunk, but the right infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…There are several classifications regarding the origin and topography of abdominal arteries [ 7 , 13 , 17 – 21 ]. The most common are various types of the celiac trunk branches [ 6 – 9 , 14 , 17 , 22 ], atypical liver vascularization [ 3 , 17 , 20 ] and differences in the territory of the mesenteric arteries [ 8 , 14 , 17 , 23 ]. The typical ‘natural’ anastomosis between the superior pancreaticoduodenal artery and the inferior pancreaticoduodenal artery forms an arterial communication named the anterior and posterior pancreaticoduodenal arcade [ 15 , 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several classifications regarding the origin and topography of abdominal arteries [ 7 , 13 , 17 – 21 ]. The most common are various types of the celiac trunk branches [ 6 – 9 , 14 , 17 , 22 ], atypical liver vascularization [ 3 , 17 , 20 ] and differences in the territory of the mesenteric arteries [ 8 , 14 , 17 , 23 ]. The typical ‘natural’ anastomosis between the superior pancreaticoduodenal artery and the inferior pancreaticoduodenal artery forms an arterial communication named the anterior and posterior pancreaticoduodenal arcade [ 15 , 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al [ 8 ] described a case where two trunks replaced the celiac trunk: the hepato-spleno-mesenteric trunk and the gastro-phrenic trunk. Yan et al [ 14 ] reported the celiac and superior mesenteric arteries arising with a common short trunk from the abdominal aorta. Iacob et al [ 9 ] described an absence of the celiac trunk, with the left gastric and the common hepatic arteries originating directly from the anterior wall of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a very close anatomical and functional connection between the celiac trunk and the SMA, and considerable variations on their branching pattern have been observed in previous studies[1-9]. Among these variations, celiomesenteric trunk (CMT) has been considered as one of the rare types, with incidence ranging from 0.4% to 2.7%[1,4,7,8,10-15].…”
Section: Introductionmentioning
confidence: 99%
“…A celiacomesenteric trunk (CMT), with common origin of the celiac and superior mesenteric arteries from the aorta, is quite rare and has incidence from 0.25% -2.7% in various studies. 1,[3][4][5][6][7]11,13,15 This anatomical variation may be accompanied by some other arterial anomalies 8 . Presence of celiacomesenteric trunk may be occasionally recognized during clinical examination, particularly when using medical imaging techniques.…”
Section: Introductionmentioning
confidence: 99%